Some stigmaeid and eupalopsellid mites from citrus orchards in Brazil (Acari : Stigmaeidae and Eupalopsellidae) - Matioli, A. L.; Ueckermann, E. A.; de Oliveira, CAL (Indira Publishing House, 2002)
Two new citrus-inhabiting species in the family Stigmaeidae, Agistemus brasiliensis n. sp. and Zetzellia malvinae n. sp., are described from citrus plants in São Paulo State, Brazil. Also, Agistemus floridanus Gonzalez is redescribed. Keys to genera of the Stigmaeidae and Eupalosellidae are provided along with a key to all species of these families associated with citrus.
Keywords: Acari; Stigmaeidae; eupalopsellidae; Agistemus; Zetzellia; Exothorhis; Cítrus; São Paulo State; Brazil